Cord blood Vitamin D levels in newborns and its correlation with anthropometric indices of baby: A cross-sectional study - Mohapatra, Jagan Nath; Doga Sherpa, T Sheten; Bedi, Nidhi (Indian Journal of Child Health, 2018)
Objectives: The objectives were to study the cord blood Vitamin D levels in term neonates and the association of Vitamin D deficiency with birth weight and crown-heel length. Materials and Methods: This cross-sectional study was performed in the department of pediatrics at the tertiary care center. All term singleton infants were included in the study. A detailed history from the mothers was taken, and complete anthropometric assessment of babies was done. Cord blood was collected, transported, and analyzed for Vitamin D levels. Data were analyzed using SPSS software. Results: A total of 202 children were enrolled. The median cord Vitamin D level was 16.0 ng/dl (interquartile range 13–18.8 ng/dl). Deficiency of Vitamin D was noted in 162 babies (80.6%) and insufficiency in 26 (13%) neonates. A total of 92.6% (151) of Vitamin D-deficient babies were low birth weight (LBW) (p